Diverging effects of mentalization based treatment for patients with borderline personality disorder and schizophrenia: an explorative comparison - Weijers, Jonas G.; van Kaam, Fleur; Selten, Jean-Paul; de Winter, Remco F. P.; ten Kate, Coriene (Frontiers in Psychiatry, 2023)
Introduction: There is robust evidence that both patients with schizophrenia (SCZ) and borderline personality disorder (BPD) display mentalizing difficulties. Less is known however about differences in the way mentalization based treatment (MBT) impacts mentalizing capacity in SCZ and BPD patients. This study compares the impact of MBT on mentalizing capacity in individuals with SCZ and BPD. Method: The thematic apperception test was used to measure mentalizing capacity. It was administered at the beginning and end of treatment to 26 patients with SCZ and 28 patients with BPD who enrolled in an 18-month long MBT program. For comparison a sample of 28 SCZ patients who did not receive MBT was also included. Using the social cognition and object-relations system, these narratives were analyzed and scored. Missing data was imputed and analyzed using intention-to-treat ANCOVAs with post-treatment measures of mentalizing capacity as dependent variables, group type as independent variable and baseline mentalizing capacities as covariates. Results: Results showed that patients with BPD showed significantly more improvement on several measures of mentalizing, including complexity of representation (ηp 2 = .50, ppooled <.001), understanding of social causality (ηp 2 = .41, ppooled < .001) and emotional investment in relationships (ηp 2 = .41, ppooled < .001) compared to patients with SCZ who received MBT. No differences were found regarding affect-tone of relationships (ηp 2 = .04, ppooled = .36). SCZ patients who received MBT showed greater performance on understanding of social causality (ηp 2 = .12, ppooled = .01) compared to SCZ patients who did not receive MBT, but no differences were observed on complexity of representations, capacity for emotional investment or affect-tone of relationships. Discussion: Patients with BPD performed better after receiving MBT on three dimensions of mentalizing capacity than SCZ patients who received MBT. Remarkably, SCZ patients who received MBT performed better on one dimension of mentalizing capacity compared to SCZ patients who did not receive MBT. Whereas MBT for BPD clearly involves improvement on most aspects of mentalizing, MBT for SCZ seems to thwart a further decline of other-oriented, cognitive mentalizing. Treatment goals should be adapted towards these disorder-specific characteristics.